2002
DOI: 10.1038/sj.ijo.0801953
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in WHO Class II–III obese men losing weight with very-low-energy diet and behaviour modification: a randomised clinical trial

Abstract: Objective: To study health-related quality of life responses to marked weight loss in WHO Class II -III (body mass index (BMI) ! 35 kg=m 2 ) obese men. Design: An 8 month randomised clinical trial with a 4 month weight loss programme (10 weeks on a very-low-energy diet (VLED) and 17 behaviour modification visits) in the treatment group and no intervention in the control group. Subjects: Nineteen men (mean age 45.9 y, mean BMI 39.3 kg=m 2 ) in the treatment group and 19 men (47.2 y, 39.4 kg=m 2 ) in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 34 publications
8
60
3
1
Order By: Relevance
“…One randomised study among obese men losing weight with very-low-energy diet and behaviour modification showed transient improvement in many domains of HRQL during the marked weight loss with the diet, but only improvements in PF, SF, and obesityrelated psychosocial problems were maintained at the end of nearly 6 months into weight maintenance phase. 10 Another study with similar weight loss programme (but a 2-y followup) showed that HRQL benefits were dependent on the success in maintaining the weight loss result. 11 A 10% weight loss at 2 y after treatment was associated with clear improvement in obesity-related psychosocial problems, PF, physical role functioning, bodily pain, GH, mental health, and vitality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One randomised study among obese men losing weight with very-low-energy diet and behaviour modification showed transient improvement in many domains of HRQL during the marked weight loss with the diet, but only improvements in PF, SF, and obesityrelated psychosocial problems were maintained at the end of nearly 6 months into weight maintenance phase. 10 Another study with similar weight loss programme (but a 2-y followup) showed that HRQL benefits were dependent on the success in maintaining the weight loss result. 11 A 10% weight loss at 2 y after treatment was associated with clear improvement in obesity-related psychosocial problems, PF, physical role functioning, bodily pain, GH, mental health, and vitality.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Weight loss achieved by surgical techniques 1 and lifestyle interventions [4][5][6][7][8][9][10][11] has improved HRQL. Diabetes with its complications has been associated with deteriorated HRQL [12][13][14][15][16] and improvement in glycaemic control with the loss of hyperglycaemic symptoms has improved HRQL in type II diabetes patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Indeed, adult studies report an inverse relationship between body mass index (BMI) and HRQOL, 2 and indicate that HRQOL improves with weight loss. [2][3][4][5] It also appears that adults seeking treatment for obesity have poorer HRQOL than non-treatment seekers after controlling for weight status. 6,7 Although lagging behind the adult literature, the last 6 years has seen an increase in the number of pediatric studies examining the relationship between obesity and HRQOL, but to our knowledge no earlier published reviews have synthesized this literature.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown in a randomised clinical trial with obese men that marked weight loss with VLED and behaviour modification led to many HRQL improvements in the short term, but with longer follow-up (nearly 6 months after treatment) only physical functioning, social functioning, and obesity-related psychosocial problems showed maintained improvement. 32 The local guidelines recommend referring obese patients to obesity clinics only if the patient has a BMI Z35 kg/m 2 with obesity-related comorbidity requiring weight loss and if previous attempts to lose weight have failed.…”
Section: Benefits and Limitationsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] The previous weight loss studies with lifestyle intervention have shown various improvements in HRQL, but the studies have usually been very short in duration. [28][29][30][31] Studies with longer follow-up have shown a more modest improvement in HRQL, 32 and to our knowledge there are no reports of follow-up over 1 y.…”
Section: Introductionmentioning
confidence: 99%